IMPLEMENTATION ANALYSIS DISASTER PREPARED SCHOOL IN ELEMENTARY SCHOOL - Bramasta, Dhi; Andriani, Ana (Universitas Sebelas Maret (UNS), 2022)
The analysis of the implementation of the disaster preparedness school aims to determine the implementation of the standby school and to find out the factors that encourage the realization of the disaster preparedness school at SDN 1 Pagerandong. Data collection with interviews, observations and documentation in order to collect data on the implementation of disaster preparedness schools and the factors that encourage the realization of disaster prepared schools. Data reduction, data presentation, drawing conclusions are the analysis in this study and supported by a regional approach to determine the condition of the research area. The results showed that the implementation of disaster preparedness schools was carried out through the integration of disaster knowledge in the school curriculum, socialization and collaboration with the community and the Regional Disaster Management Agency. The school building was built right above the ravine, where the position of the ravine was right next to the school building wall. Supported by the condition of the area with hilly morphology, so it is easy to experience soil movement and landslides occur. This condition is a factor in the realization of a disaster preparedness school at Pagerandong State 1 Elementary School.